Perilaku Tidak Etis Dan Kesesuaian Kompensasi : Mengukur Kecenderungan Kecurangan Akuntansi - sulfati, andi; Ariska, Nur (Jurnal Ilmiah Bongaya, 2021)
This study aims to determine whether unethical behavior and suitability of compensation have an effect on the tendency of accounting Vraud at BRI Panakkukang Branch, Makassar City. Data collection using primary Datta obtained from a questionnaire using nonprobability sampling technique with a sample calculation formula using the Slovin formula. The population is all employees of the BRI Panakkukang Branch Makassar City, totaling 125 employees. While the samples taken were 56 respondents. The results of the questionnaire have been tested for validity and reliability, as well as tested for classical assumptions in the form of normaIity assumptions and heteroscedasticity assumptions. Methods of Datta analysis using multiple linear regression techniques.The results of the research simultaneously (statistical test F) show that unethical behavior and suitability of compensation have an effect on the tendency of accounting Vraud. The results of the research partially (T-statistic T) show that Unethical Behavior has a positive and significant effect on Accounting Vraud Tendency, whereas Compensation Suitability has a negative effect on Accounting Vraud Tendency.